EXAMINING THE IMPACT OF PROMOTION AND SERVICE QUALITY ON CUSTOMER SAVINGS DECISIONS AT BANK SULSELBAR SYARIAH IN MAMUJU REGENCY - Taslim R, Suwanti; Iwan Adinugroho (SEAN Institute, 2023)
This study investigates the factors influencing customer deposit decisions at Bank Sulselbar Syariah in Mamuju Regency. Using observation, interviews, questionnaires, and documentation, the research analyzes the impact of Promotion and Service Quality on customer choices. Results reveal that both variables positively and significantly affect deposit decisions. Effective promotions and high-quality services influence customers to select the bank. Additionally, a simultaneous test demonstrates their combined significant influence. This highlights the importance of coordinated promotional efforts and exceptional service quality in shaping customer decisions. The findings offer practical insights for enhancing marketing strategies and services in the banking sector, fostering customer trust, satisfaction, and increased deposits.